A Knowledgebase Editor Using Semantic Web Technologies - Bakraceski, Goran; Stojanov, Riste; Jovanovik, Milosh; Trajanov, Dimitar (Institute of Informatics, Skopje, Macedonia, 2010)
We agree that a semi - structured data model offers the right balance of rich structure and flexible schema allowing users to store and manage data as they prefer, making the access as easy as possible. For that reason we build this system, which exposes the richness and flexibility of the data model, offering natural access to the data and hides the specifics of schema, tuples and database queries. This system uses semantic web technologies for data representation, providing form and text based data entry and retrieval. Data is stored in RDF (Resource Definition Framework) format [1], while the forms are generated from the OWL (Ontology Web Language) data definition [2]. The OWL based guiding is provided for the text entry via suggestions. Users with poor knowledge in OWL and RDF can use this system for defining the format of their data, by entering and altering OWL classes, and manipulate with their instances.
Keywords: silverlight application, semantic web, knowledgebase editor